Cardiovascular Effects of Longer-Term, High-Dose OROS Methylphenidate in Adolescents with ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The short-term and longer-term cardiovascular safety of high daily doses of OROS methylphenidate (MPH) of up to 1.5 mg/kg in 114 adolescents with ADHD is reported from Massachusetts General Hospital, Boston, MA.